Integração espacial no mercado brasileiro de café arábica - Fernando Tadeu Pongelupe Nogueira (Nova Economia, 2009)
This study analyzes spatial integration in the arabica coffee market of the two main producer states in Brazil. The results of the Dickey-Fuller Augmented (DFA) unit root test show that all price series are integrated of first order, I(1). The results of the Johansen co-integration test suggest that all series are co-integrated. It can be concluded, thus, that the coffee markets of the main producer regions in the States of Minas Gerais and São Paulo are spatially integrated, which means that supply and demand shocks in one of these markets affect the coffee prices in the other markets. Another outcome of this research, resulting from the estimation of an error correction model and the application of the Granger causality test, is that the Cerrado region in the State of Minas Gerais Granger-causes the prices in the other regions. This result contradicts the expectation that the South of Minas region, one of the main producers and exporters in Brazil, would lead the remaining regions. Therefore, the results of this research suggest that the Brazilian coffee market is efficient, since information has flowed rapidly among the market agents, allowing arbitrage and the Law of One Price to work properly.